Retail Pharmacy Market Structure and Performance - John M. Brooks; William R. Doucette; Shaowei Wan; Donald G. Klepser (SAGE Publishing, 2008)
Substantial variation has been observed in the use of prescription drugs from retail pharmacies, the level of services provided by retail pharmacies, and the prices paid for prescriptions from retail pharmacies. It is not clear whether local area retail pharmacy market structures affect these pharmacy outcomes. The goal of this paper is to discuss the potential research avenues to address these issues. The discussion provides: 1) background on the retail pharmacy and its place within the pharmaceutical supply chain; 2) a discussion of the data that are available to address these issues and the measures that can be developed from these data; and 3) a review of existing research findings and gaps in knowledge.